Conducting transition metal nitride thin films with tailored cell sizes: the case of δ-TixTa1−xN - Abadias, Gregory; Lekka, Christina E.; Koutsokeras, Loukas E. (My University, 2008)
We present results on the stability and tailoring of the cell size of conducting δ- Tix Ta1-x N obtained by film growth and ab initio calculations. Despite the limited solubility of Ta in Ti, we show that TiN and TaN are soluble due to the hybrization of the d and sp electrons of the metal and N, respectively, that stabilizes the ternary system to the rocksalt structure. The stress-free cell sizes follow the Vegard's rule; nevertheless, process-dependent stresses expand the cell size of the as-grown films. The electronic properties of δ- Tix Ta1-x N films (ρ =180 cm) are similar to those of TiN and TaN
Keywords: Cells--Growth; Liquid phase epitaxy; Metals; Nitrides; Tantalum; Molecular beam epitaxy